Measurement of sequential Υ suppression in Au+Au collisions at √sNN=200 GeV with the STAR experiment - Aboona, Bassam; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physical review letters, 2023)
We report on measurements of sequential Υ suppression in Au+Au collisions at √sNN=200 GeV with the STAR detector at the Relativistic Heavy Ion Collider (RHIC) through both the dielectron and dimuon decay channels. In the 0%-60% centrality class, the nuclear modification factors (RAA), which quantify the level of yield suppression in heavy-ion collisions compared to p+p collisions, for Υ(1S) and Υ(2S) are 0.40±0.03(stat)±0.03(sys)±0.09(norm) and 0.26±0.08(stat)±0.02(sys)±0.06(norm), respectively, while the upper limit of the Υ(3S) RAA is 0.17 at a 95% confidence level. This provides experimental evidence that the Υ(3S) is significantly more suppressed than the Υ(1S) at RHIC. The level of suppression for Υ(1S) is comparable to that observed at the much higher collision energy at the Large Hadron Collider. These results point to the creation of a medium at RHIC whose temperature is sufficiently high to strongly suppress excited Υ states.
*STAR Collaboration: B.E. Aboona, I.M. Deppner, N. Herrmann, Y.H. Leung, Y. Söhngen, P.C. Weidenkaff [und 367 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, NN ist dabei tiefgestellt
Gesehen am 26.06.2023